2005
DOI: 10.1902/jop.2005.76.6.956
|View full text |Cite
|
Sign up to set email alerts
|

Nitric Oxide Synthase Inhibition Prevents Alveolar Bone Resorption in Experimental Periodontitis in Rats

Abstract: These data provide evidence that NOS inhibitors prevent inflammatory bone resorption in experimental periodontitis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
89
0
2

Year Published

2006
2006
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 100 publications
(101 citation statements)
references
References 42 publications
10
89
0
2
Order By: Relevance
“…In this regard it has been reported that bone resorption in rats with induced periodontal disease could be prevented with isosorbid, an iNOS inhibitor (33,34), as well as with mercaptoethylguanidine (25). Other inhibitors used have included aminoguanidine (35) and the enzyme arginase, which competes with the substrate (L-arginine), thus reducing NO production (23).…”
Section: Discussionmentioning
confidence: 99%
“…In this regard it has been reported that bone resorption in rats with induced periodontal disease could be prevented with isosorbid, an iNOS inhibitor (33,34), as well as with mercaptoethylguanidine (25). Other inhibitors used have included aminoguanidine (35) and the enzyme arginase, which competes with the substrate (L-arginine), thus reducing NO production (23).…”
Section: Discussionmentioning
confidence: 99%
“…Another interesting fact is that the absence of this cytokine impairs PGE2 and NO production (Hurwitz et al, 1997;Ralston & Grabowski, 1996), which favors anabolic activity in the bone mechanotransduction pathway mentioned in the previous section. Nitric oxide (NO) increases root and bone resorption in orthodontics (Akin, Gurton & Olmez, 2004;Leitao et al, 2005;Leitao et al, 2004), an effect opposite to that in orthopedic reactions. Currently, there is no proven explanation for these contradictions.…”
Section: Biological Factors In Rate Of Tooth Movement and Errmentioning
confidence: 99%
“…Six-micrometer thick sections obtained from 6 animals in each experimental group, corresponding to the area between the first and second molars where the ligature had been placed, were examined by light microscopy. A 0 to 3 scale was used for analysis: 0, absence of or only mild cell infiltration (the inflammatory cell infiltration is sparse and restricted to the region of the marginal gingiva), preserved alveolar process and cementum; 1, moderate cell infiltration (the inflammatory cell infiltration is present over the entire inserted gingiva), minor alveolar process resorption and intact cementum; 2, severe cell infiltration (the inflammatory cell infiltration is present in both the gingivae and the periodontal ligament), extensive degradation of the alveolar process, and partial destruction of cementum; 3, severe cell infiltration, total destruction of the alveolar process and severe destruction of the cementum (24).…”
Section: Histopathological Analysismentioning
confidence: 99%